Organizacija in organiziranje (University of Maribor Press, 2025)
Organization and organizing. Modern society is a society of organisations. Organisations are places where people find themselves in different forms, different activities and pursuing different interests and goals. In the same way, the question of organisation, through its institutional, instrumental definition and through the design of the organisation, has been evolving since the very beginnings of scientific research in the field of organisational studies. Issues relating to organisation and organising are rooted first and foremost in human perception and understanding of the laws of organisations, which must be taken into account both formally and informally. In the scientific monograph ’Organisation and Organising’, we have brought together chapters that have been authored and co-authored by university teachers and staff and doctoral students. The thematic strands are linked to the fields of organisation, taking into account the human resources, process and information aspects.